(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
تتناول هذه الدراسة ديوان " أنشودة المطر " لبدر شاكر السيّاب ، بناءً على ما وظّف فيه من أساطير كثيرة متنوعة ، بصورة فاقت ما في دواوينه الأخرى ، ربما لعودة هذا الديوان زمنياً إلى المرحلة التي كان قد حصَّل فيها ما يكفي من هذه الثقافة . علماً أننا حاولنا من خلال هذا التوظيف الأسطوري أن نتقصى ما يكمن خلفه من تعبير الشاعر عن الحياة والموت اللذين شغلاه عبر زمانه على الصعيدين الفردي الذي يخصه ، والعام الذي يخص العالم الخارجي من حوله ، بفعل ما توالى عليهما من ظروف . وقد بينَّا بهذا الصدد كيف استعان الشاعر بالأساطير الثنائية التي انطوى كل منها على هاتين الدلالتين في آن واحد : الحياة والموت ، بالرغم من تباعدهما ، وكذلك كيف استعان بالأساطير التي اقتصرت على دلالة الموت ، الموت الذي ابتغى الشاعر لدى إضافته إلى الموت في الأساطير الثنائية تغليبه في الديوان على الحياة التي تقابله ، ذلك انعكاساً لغلبة الموت على الحياة في ذاته الفردية، ووطنه العراق، والبقاع الكثيرة عبر أرجاء الأرض . This study handles the Divan “Song of Ring” ofBadr Shaker Al-Sayab, based on the many various myths he had employed in this Divan, in a way that exceeded what came in his other Divans, perhaps because this Divan dates to the period when he had acquired enough of this culture. Through this mythical employment, we have tried to investigate what lies behind the Poet’s expression of life and death that occupied his mind throughout his life at the individual level of his own and at the general level which belongs to the external world around him, due to the circumstances that came successively on both levels. In this respect, we have shown how the Poet resorted to the dual myths which each had implied these two indications simultaneously: life and death, despite the contrast between them ; and also how he resorted to the myths which were confined to the indication of death which the Poet aimed to show in the Divan as predominant over life, as reflection for death predominance over life within his personal self and in his Homeland, Iraq, and many other parts of the world.